Assessment of the strength of the cabin mounting elements of the high-capacity wheeled chassis - Shalupina P.I.; Artyomova A.A. (Научно-технический вестник Брянского государственного университета)
The article deals with the issues of modeling the stress-strain state of the attachment points of the cab of a wheeled chassis of high load capacity. The main design loads are determined. Geometric and computational finite element models are constructed, taking into account the features of the metal structure. The technique of gluing elements of the grid model is applied. The contact interaction of the parts is taken into account. Based on the calculations performed, conclusions are drawn about the compliance of the developed structure with the strength requirements.